2020
DOI: 10.1002/pat.4853
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation on oil diffusion mechanisms in nano‐organic‐montmorillonite modified caster oil‐based polyurethane foam for oil/water separation

Abstract: To improve the oil absorbency of caster oil-based polyurethane foam, nano-organicmontmorillonite (OMMT) was used for the additives. The aim of this study is to evaluate the oil diffusion mechanism and dispersion uniformity of OMMT modified caster oil-based polyurethane (MPU) using experiments and molecular dynamic simulation.Molecule movement and molecule trajectory of oil was investigated by molecular dynamic simulation and numerical simulation. According to the quantitative analyzing results, the diffusion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…23,24 Moreover, they also can be added into PUF or sprayed on the surface of PUF as a surfactant to achieve superhydrophobicity. [25][26][27] The addition of additives with hydrophobic properties can improve the overall hydrophobicity of PUF, 28 especially nanoparticles with adjustable surface function, good structural stability, and high adsorption capacity; they are widely used in textile, biomedicine, and environmental protection. [29][30][31] In recent years, superhydrophobic nanomaterials have played a good role in oil-water separation.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Moreover, they also can be added into PUF or sprayed on the surface of PUF as a surfactant to achieve superhydrophobicity. [25][26][27] The addition of additives with hydrophobic properties can improve the overall hydrophobicity of PUF, 28 especially nanoparticles with adjustable surface function, good structural stability, and high adsorption capacity; they are widely used in textile, biomedicine, and environmental protection. [29][30][31] In recent years, superhydrophobic nanomaterials have played a good role in oil-water separation.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the crystallization process of polyurethane at a fixed temperature can be divided into three steps, and the crystallization rate decreased with the decrease of crystal temperature. Zhou and Huang 14 used experiments MD simulation to investigate the oil diffusion mechanism of nano‐organic‐montmorillonite (OMMT) modified castor oil‐based polyurethane (MPU). They put forward the diffusion model of OMMT/MPU and pointed out that the main reason for crude oil diffusion and adsorption was van der Waals force.…”
Section: Introductionmentioning
confidence: 99%
“…These include oil refining and drilling industries, 2 which produce large quantities of oil effluent in the seas. Some of these oily pollutants in the seas are cleared by the natural process, 3 but large quantities of these pollutants remain in the marine ecosystem, which must be eliminated due to their adverse environmental and toxic effects 4,5 . The mixture of water and oil is physically divided into three categories based on the droplets size: free oil (≥150 μm), dispersed oil (20‐150 μm) and oil emulsion (≤20 μm) 1 .…”
Section: Introductionmentioning
confidence: 99%